Modelling Influence on Bending Behaviour Simulation of the Poly(Lactic Acid) Structures, 3D Printed - Catana, Dorin; Brus, Denisa Iulia; Pop, Mihai Alin (Polymers, 2023)
The paper presents the influence of the loading modelling on the simulation process results of the bending behaviour for 3D printed structures. The study is done on structures having different geometries of the cross section, and the type of structure is bar or tube. The materials used for 3D printing are poly(lactic) acid and poly(lactic acid) mixed with glass fibres. The simulation was carried out both based on a simple modelling (schematization) of the bending loading and a complex one. The complex modelling reproduces the bending of 3D printed structures more accurately but is also more time-consuming for the computer-aided design stage. Analysis of the study results shows that in terms of the Von Mises stresses determined by simulation, they are in line with those of the tests but with a slight advantage for the complex modelling compared to the simple one. In terms of deformations, the simulation introduces errors compared to the test results, but the source of the errors is the high elasticity of some 3D printed structures. The study also shows that the high elasticity is due to both the shape of the structure cross section and its arrangement during the bending test.
Keywords: additive manufacturing; poly(lactic acid); bending; simulation